The Relationship Between Peer Social Suport and Family Support With Academic Stress Among Students At SMAN 5 Jeneponto - Masahuddin La; Edy Supardi; Ayu Paneo; Iis Ismayanti (Innovative Approaches in Health Science Journal, 2026)
Background: Academic stress is a psychological pressure experienced by students due to high academic demands. One factor that may influence academic stress is social support, including support from peers and family.. Objective:To determine whether peer social support and family support are associated with academic stress among students at SMAN 5 Jeneponto. Methods: This study used a quantitative cross-sectional design. The sample consisted of 75 students selected using accidental sampling. Data were collected using questionnaires and analyzed using the Chi-square test. Results: Of the students, 68.0% reported high peer support and 76.0% reported high family support. A total of 56.0% were in the low academic stress category, while 44.0% were in the high academic stress category. Bivariate analysis showed a significant association between peer social support and academic stress (p = 0.000) and between family support and academic stress (p = 0.000). Higher support was associated with lower academic stress levels. These findings highlight the importance of strengthening support from peers and family to help students manage academic pressure in healthier and more adaptive ways. Conclusion: There were significant relationships between peer social support and family support with academic stress among students at SMAN 5 Jeneponto. Most students reported high peer support (68.0%) and high family support (76.0%); however, 44.0% of students still experienced high academic stress. Keywords: Social Support, Peer Group, Family Support, Academic Stress